Valuation of alternatives in no definite circumstances/Alternatyvų vertinimas neapibrėžtumo sąlygomis - Gaučas, Paulius; Zavadskas, Edmundas Kazimieras (Journal of Civil Engineering and Management, 2001)
Task of decisions-making in constructing industry becomes more difficult because of rapid technical growth. According to aims, circumstances and opportunity decisions are determined. Disagreement situation arises at this point. Apprising opportunities and influence of circumstances of aims, they are often contradicting each other. In decisions-making practice, many possible results of accepted decisions must be valued. Selecting operations from a lot of alternatives this valuation lead to several criteria employment. In other words, decision must be optimized not with one, but with several objective functions. Expression “trying to reach maximum effect with minimum expense” that often occurs, means making decision by two criteria. But brought up aims often contradict each other. This mean that disagreement situation arises, which is understandable as indefinite [2, 4]. To solve the problem the fuzzy sets theory can be used und a new model can be made. Trying to estimate the aims of conflicts, the circumstances that influence the decision are divided into two groups. The first group – circumstances of inherent influence – defines what a decision-maker must attain (for example, to maximize quality). The second group – circumstances of outward influence – defines what a decision-maker must estimate as a limitation (for example, to minimize price). Dependence between inherent and outward circumstances in this step is formed. There are no clear limit in fuzzy sets theory between dependence (circumstance 1) and independence (circumstance 0) of elements to definite set. Dependence degree of element X to A set, is described by μA(x) function (1), (2). The valuation in fuzzy sets theory takes place in three levels. In first level meanings of dependence for inherent circumstances is calculated (1), (2), and matrix is determined (Table 4). According to formula (4) dependence degree of each alternative is calculated. In the second level meanings of dependence for outward circumstances are calculated according the formula (1), (2) and the matrix is filled in (Table 5). In third level, the results of first two levels are summed. Using operator of minimum general matrix of decision-making is determined (Table 6). Minimax principle makes the decision, and max value is selected from the minimal values. The received result is optimum, because it is to satisfy aim apprizing the conflict. [7] In the paper presented example of possible versions valuation of motorbuses and trucks under construction service in Vilnius district. This method may be used to make decisions, when the task is of conflict character. Competently distributing circumstances of influence or parameters of valuation by two aspects (inherent and outward) the means of conflict character can be explained and interpretation using described method can be made. Article in Lithuanian. First Published Online: 30 Jul 2012